Symposium 7: The Politics of Networked learning - Jones, Chris; Clegg, Sue; Steel, John; Conole, Grainne; Roberts, George (Proceedings of the International Conference on Networked Learning, 2002)
Networked learning is part of an emergent networked society. As such networked learning forms part of a wider debate concerning the nature of social processes, power and culture and their relationships with technology. The literature surrounding networked learning still reflects a technological determinist view. This paper takes issue with this view of the relationship between technology and social forms. The context of higher education has been changing alongside the introduction of new technologies into education. The paper looks at the United Kingdom as an example of the way in which political issues impact on networked learning. The paper tries to establish what choices are being made at the level of national governments by examining two large policy initiatives as examples of current policy. Papers: Is there a policy for networked learning? Chris Jones Flexibility as Myth? New Technologies and Post-Fordism in Higher Education Sue Clegg and John Steel Applying National Politics: Linking Strategy with Local Developments Grainne Conole Complexity, Uncertainty and Autonomy: the Politics of Networked Learning George Roberts